Effect of Material Variability on the Structural Behavior of Reinforced Concrete Beams with Openings: A Numerical Application Using Random Fields and Mazars Concrete Model - Halim Muhammad Rifki; Nuraziz Handika; Rendy Thamrin; Taufik (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study aims to evaluate the influence of material heterogeneity on the behaviour of reinforced concrete beams with and without openings using a random field approach based on the Turning Band Method (TBM). A three-dimensional nonlinear finite element model was developed using the Perfect Interface (PI) assumption and validated against experimental data for reinforced concrete beams with different longitudinal reinforcement ratios and a 4-inch opening diameter. Material heterogeneity was represented using TBM-generated random fields with five random field realizations, and the analyses were performed in Cast3M using the Mazars damage model with three-dimensional CUB8 elements. The results indicate that the combined effects of openings and material heterogeneity produce variations in structural response that cannot be fully represented by the conventional assumption of homogeneous material properties. The influence of material heterogeneity was more pronounced in the post-peak response of beams without openings, whereas geometric discontinuities governed the failure mechanism of beams with openings. Incorporating TBM-based random fields into the nonlinear finite element model provides a more realistic representation of reinforced concrete behaviour by accounting for the influence of material heterogeneity, particularly on post-peak response and damage evolution.